2014
DOI: 10.1016/j.neo.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Selumetinib (AZD6244) in Colorectal Cancer Cell Lines is Mediated by p70S6K and RPS6 Activation

Abstract: Selumetinib (AZD6244, ARRY-142886) is a MEK1/2 inhibitor that has gained interest as an anti-tumour agent. We have determined the degree of sensitivity/resistance to Selumetinib in a panel of colorectal cancer cell lines using cell proliferation and soft agar assays. Sensitive cell lines underwent G1 arrest, whereas Selumetinib had no effect on the cell cycle of resistant cells. Some of the resistant cell lines showed high levels of ERK1/2 phosphorylation in the absence of serum. Selumetinib inhibited phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…In agreement with these previous findings, in vitro overexpression of p70S6K was also shown to promote cellular proliferation and inhibit apoptosis in breast cancer [48]. Conversely, RNA interference-mediated knockdown of p70S6K decreased the cellular proliferation of human glioblastoma cell lines U251 [49] and sensitized resistant colon cancer cells to selumetinib [50]. Dhar et al showed that cisplatin caused a caspase-3-dependent cleavage of p70S6K and that proteolytic cleavage is important for cisplatin-induced apoptosis in H69 and A549 colon cancer cells [32].…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with these previous findings, in vitro overexpression of p70S6K was also shown to promote cellular proliferation and inhibit apoptosis in breast cancer [48]. Conversely, RNA interference-mediated knockdown of p70S6K decreased the cellular proliferation of human glioblastoma cell lines U251 [49] and sensitized resistant colon cancer cells to selumetinib [50]. Dhar et al showed that cisplatin caused a caspase-3-dependent cleavage of p70S6K and that proteolytic cleavage is important for cisplatin-induced apoptosis in H69 and A549 colon cancer cells [32].…”
Section: Discussionsupporting
confidence: 89%
“…Both, free and immobilized, CLytA-DAAO chimera are able to induce cell death by increasing ROS production, which caused DNA damage in several colon carcinoma and pancreatic adenocarcinoma cell lines as well as in glioblastoma cell lines derived from primary cultures obtained in our laboratory directly from glioblastoma patients, at doses that are safe for non-tumor cells. Interestingly, the cell death evoked by the enzyme could be executed by apoptotic or necrotic mechanisms depending on the tumor origin.The reasons to select these types of tumors in our study were their frequency, mortality, and resistance to other treatments and also our laboratory experience, since we have been working in these models for many years [19][20][21][22][23]. This localized therapy reduces the dose of drug needed, improving the effectiveness and decreasing adverse effects.…”
mentioning
confidence: 99%
“…The reasons to select these types of tumors in our study were their frequency, mortality, and resistance to other treatments and also our laboratory experience, since we have been working in these models for many years [19][20][21][22][23]. This localized therapy reduces the dose of drug needed, improving the effectiveness and decreasing adverse effects.…”
mentioning
confidence: 99%
“…Specifically, BTF3 was confirmed aberrantly in various cancer tissues such as gastric cancer tissues [47,48], prostate cancer tissues [49], colorectal cancer tissues [50] and pancreatic cancer cells [51]; RPS16 was found dysregulated in disc degeneration, which is one of the main causes of low back pain [52]; HSF1 influenced the expression of heat shock proteins as well as other activities like the induction of tumor suppressor genes, signal transduction pathway, and glucose metabolism. Its associations with gastric cancer [53], breast cancer and two of the studied SNPs correlated significantly with cancer development [54] have been proved; RPS6 was declared closely relevant to the nonsmall cell lung cancer (NSCLC) [55], the renal cell carcinoma [56] and some other cancers [57,58]; MAPKAPK2 was demonstrated to contribute to tumor progression by promoting M2 macrophage polarization and tumor angiogenesis [59].…”
Section: Discussionmentioning
confidence: 98%